Simplified Methods for Microtiter Based Analysis of In Vitro Antioxidant Activity (Asian Journal of Pharmaceutics (AJP), 2017)
Context: The research in exploring the antioxidant activity of pharmaceuticals has recently been increased considerably and to determine such property a variety of testing methods are available. However, the major drawback of these conventional tests is their large reaction volumes varying from 2 to 6 ml that in turn demand high quantity of reagents and biological resources. Aims: Thus, this work was focused for optimization of routinely used five antioxidant experiments such as superoxide radical (O2.− ) inhibition, 2, 2-diphenyl-1-picrylhydrazyl (DPPH) quenching, 2′-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS.+) scavenging, chelating ability of ferrous ion and reducing power by means of 96-well plates in minimal reaction volume ranging from 60 to 200 μl. Subjects and Methods: To authenticate the processes some renowned standards such as ascorbic acid, butylated hydroxyanisole, Trolox as well as ethylenediaminetetraacetic acid were used, and their calibration curves were prepared. Results: Analysis depicted similar activities of all references as reported by traditional protocols suggesting validation of standardized procedures. Conclusion: Thus, the recommended systems clearly improve original one in a number of ways. First, the methods provide concurrent multi-sample investigation with automatic data storage. Second, the approach is time-saving with the use of a multichannel pipette. Third, assays are inexpensive as the use of chemicals is reduced by 10 times. Fourth, the investigating pure compounds or extracts are required in low quantity. Fifth, except O2.− quenching assay, all the methods are applicable to lipophilic and aqueous components both